Hubungan Pemahaman Gaya Bahasa dalam Cerita Rakyat terhadap Minat Baca Siswa Kelas V Sekoah Dasar Negeri 17 Kota Bengkulu - Nanang Muttaqin Ibnu Prayitno; Abdul Muktadir; Ansyori Gunawan (JURIDIKDAS, 2019)
The aims in this study to determines the correlation between understanding of folklore language style against reading interest on the V grade students in SDN 17 Bengkulu city. Research method using correlational with quantitative. The population are 46 people located in SDN 17 bengkulu city. The sampling technique used saturated side (census. Questionnaire and data is a data collection technique with a questionnaire for assessing reading interest in the home of 20 item statements while the test for understanding the style with 5 questions that serve as benchmark. Data analysis techniques use the correlation statistics "Product Moment". The results showed that there is a correlation between understanding the style of language in folklore against reading interest. It is proved by rcount = 0,600 bigger than rtable that is 0,355 with significant level 5%. Thus, the hypothesis is proved and accepted. It’s means that reading foklore, making someone will increase interest reading, then someone will understand the style of Language by it self.